(untitled) (Window of Public Health Journal, 2025)
Based on data from the blood transfusion of the South Sulawesi Provincial Health Office in 2023, in February the number of students who took part in blood donations were 26 people, 6 months totaling 38 people, and 11 months totaling 25 people. In 2024 the new blood donor activity was carried out twice, February 14 people and 21 people in May one of the factors that influenced the lack of blood donation was the lack of knowledge. Thus the researcher argues that with this research can increase respondents’ knowledge about blood donors so that students can find out the importance of blood donation. The purpose of this study is to determine the factor of blood donor interest in students in students in the Indonesian Muslim University Community Health Study Program. This research uses a type of quantitative research, with an analytical descriptive approach. Where this research is used to see what are the factors causing the lack of blood donor interest in students in the Indonesian Muslim University Community Health Study Program. The sampling technique in this study was the sample sampling used 248 respondents. The results in this study were there was no knowledge of knowledge of blood donor interests, the relationship of attitude towards blood donor interests, the relationship of behavior towards the interest of blood donation, no relationship of health workers to the interests of blood donors, so that there was still a need for routine campaigns in the environment Campus to provide correct information about blood donors, including the benefits, procedures, and relevant medical facts.